SISTEM PENGENDALI HAMA PADA TANAMAN PADI BERBASIS IoT MENGGUNAKAN TENAGA SURYA PADA MASYARAKAT DESA WUKIRSARI - Maulana Wahid, Rindo; Santoso, Gatot; Hani, Slamet; Hamzah, Amir; Raharjo, Suwanto; Setyaningsih, Emy (Universitas Sahid Surakarta, 2023)
The rice pest control system based on the Internet of Things (IoT) and powered by Solar Power Plants (PLTS) is an innovative solution aimed at enhancing productivity and sustainability in Indonesia's agricultural sector. This community service project, conducted in Wukirsari Village, Kapanewon Cangkringan, Sleman Regency, primarily focuses on addressing pest issues and technological limitations. The designed device integrates ultrasonic sensors and UV light controlled by the ESP32 microcontroller, utilizing PLTS as the energy source. The system can be accessed and controlled remotely via the Blynk server, making monitoring and control more efficient and sustainable. The research methodology includes information gathering, device design, testing, and comprehensive evaluation. Integration with PLTS ensures the system uses environmentally friendly energy. The test results indicate that the device effectively monitors and controls pests while providing ease of management with a responsive modern tool. The device operates in real-time and is highly responsive, supported by solar panels with a capacity of 920W, capable of fully charging the battery in approximately 2.6 hours. This allows the device to operate continuously for 24 hours. The implementation of this technology not only demonstrates reliability in addressing pest issues but also proves that the system can function sustainably, supporting agricultural productivity, and providing significant benefits to farmers in Wukirsari Village.